Stirring up the muck: the systematics of soft-sediment Fionidae (Nudibranchia: Aeolidina) from the tropical Indo-Pacific - Kim,Ashley Y.; Donohoo,Samantha A.; Gosliner,Terrence M. (PeerJ, 2024)
The tropical Indo-Pacific aeolid nudibranchs of the Fionidae are poorly known and have not been studied in a concerted manner. Many undescribed species are found throughout the Indian and Pacific Oceans and are concentrated in the Coral Triangle. With the recent publication of a revised systematic arrangement of the Fionidae, documentation and description of new taxa of Fionidae is especially warranted. Here we describe Tenellia bughaw Kim & Gosliner sp. nov., Tenellia puti Kim & Gosliner sp. nov., Tenellia nakapila Kim & Gosliner sp. nov., Abronica payaso Kim & Gosliner, sp. nov. and Abronica turon Gosliner & Kim sp. nov. from the waters of the Coral Triangle. Their phylogenetic placement in Fionidae is reviewed using three genes: cytochrome oxidase I (COI), 16s rRNA, and histone 3 (H3) in a Bayesian and maximum likelihood framework. A redescription of Tenellia yamasui (Hamatani, 1993) is also provided to clarify its distinctiveness from T. bughaw and T. puti. This study confirms that all four known species of Abronica are characterized by having an acutely pointed curved penial stylet, thus confirming a unique morphological synapomorphy for members of this genus. A discussion on conflicts in the classification of fionid aeolid nudibranchs addresses concerns with extreme splitting based on novel innovations that emphasize evolutionary novelty over phyletic kinship. Instead, a more conservative approach is suggested, especially within the context of taxa that still have much undocumented primary diversity.
Keywords: Phylogenetics; Indo-Pacific; Nudibranchia; Biodiversity; Systematics; Classification